Comunicação visual como recurso de apoio a prevenção e ao controle das infecções hospitalares - valor da lavagem das mãos realçado por figuras e mensagens ilustrativas - Russo, Sérgio; Baldy, José Luís da Silveira (Semina: Ciências Agrárias, 1984)
Proposition of visual communication, by illustrative figures and messages appealing to jokes and expressionism, as a mean to reduce the incidence of the hospital infections. The content of the messages is related to the value of the handwashing with soap and water to reach the onlookers, emphasizing the need for the physicians, nurses, students and the remaining technicians and therapists to take to the hand-washing, berfore and after the contacts with the patients, as a basic measure and a routine procedure.